A new distribution record of Diplomeris hirsute (Lindl.) Lindl. (Orchidaceae) from Arghakhanchi District, Nepal - Panthi, Mohan Prasad; Chaudhary, Ram Prasad (Journal of Natural History Museum, 2008)
A new distribution with small population of Diplomeris hirsute (Lindl.) Lindl. is reported from Arghakhanchi district, Nepal. Previously it was reported only from limited areas of Eastern and central Nepal to Bagmati Zone. Previous collections and distribution are compared with this present collection. Protection and conservation of this rare ground orchid is recommended at local level. J. Nat. Hist. Mus. Vol.22, 2005 p.129-133